Łużyce w wybranych polskich koncepcjach polityczno-prawnych po drugiej wojnie światowej - Krychowski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Polish interest in the area of Lusatia dates back to the 18th century, but it significantly intensified in the interwar period, along with the development of Polish western thought. An interesting aspect of Polish-Sorbian contacts was intelligence cooperation in the interwar period, which was interrupted by the outbreak of the war. With the end of World War II approaching, the issue of shifting Poland’s western border, as well as the reorganization of Germany, was becoming more and more frequent in various political circles. The Sorbian cause was also debated. It was postulated that Lusatia should become an independent state, be incorporated into Poland or Czechoslovakia or remain within the borders of Germany with the status of autonomy. It should be emphasized that the Sorbian subject in Poland was clearly related to the issue of the western border. Despite their efforts, the Sorbs were unable to internationalize their aspirations and to convince the Soviet authorities to accept them. With the creation of East Germany, the chance of some form of independence for the Sorbian people or merging with another Slavic country became very small.
Keywords: Łużyce; Serbołużyczanie; Polska; Niemcy; Czechy; granica zachodnia; druga wojna światowa; Lužicâ; serbolužičani; Polʹŝa; Čehoslovaččina; zahìdnij kordon; II Svìtova vìjna